RELOKASI PEDAGANG PASAR TRADISIONAL PADA KAWASAN GIANT PANAM - Formen Gultom; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted at the Giant Panam Traditional Market, Tampan District, Pekanbaru City with the following problems: (1) How is the Economic Condition of the Giant Panam Traditional Market Traders in Tampan District Before Market Relocation? (2) How is the Economic Condition of the Giant Panam Traditional Market Traders in Tampan Subdistrict After Market Relocation? The purpose of this study is to determine the economic condition of market traders before relocation and to find out how the economic situation is after relocation. This research is a quantitative research, the sample in this study is traders in the Giant Panam traditional market. The sample of this study was taken with the Slovin formula as many as 60 respondents. To collect data, researchers used documentation guidelines and questionnaires. The results of this study explain that the economic situation of market traders. increased after market relocation. Keywords : Economic Impact, Traditional Markets, Relocation Policy.